A systematic review of medical interventions for oral submucous fibrosis and future research opportunities - Kerr, AR; Warnakulasuriya, S; Mighell, AJ; Dietrich, T; Nasser, M; Rimal, J; Jalil, A; Bornstein, MM; Nagao, T; Fortune, F; Hazarey, VH; Reichart, PA; et al. (Oral diseases, 2011)
Oral Diseases (2011) 17 (Suppl. 1), 42–57 Oral submucous fibrosis (OSF) is a chronic, insidious disease caused by areca nut use, and is associated with both significant morbidity (including pain and reduced oral opening) and an increased risk for malignancy. This systematic review explored and updated the current medical (i.e., non‐surgical) interventions available for the management of OSF. Of the 27 published medical interventions, there were four randomized controlled trials. The overall quality of these randomized controlled studies was assessed using the GRADE approach and significant limitations that challenged the conclusions were found. However, this review was valuable in terms of identifying opportunities to provide recommendations for future research, in terms of the populations to research, the types of interventions needed, the types of outcomes to be measured, the study designs needed, and the infrastructure required to conduct studies. The next step is to initiate a pathway for a low‐cost research plan leading to the development of a brief protocol for future clinical trials in this field, with an emphasis on conducting studies in regions of the world where OSF is prevalent.